2018
DOI: 10.1051/matecconf/201822901008
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of flood disaster response preparedness in Gampong Seulalah Langsa Lama Sub-District Langsa City

Abstract: Langsa City is one of the City in Aceh Province that suffer from flood disaster almost every year. This research aims to analyze the extent of preparedness of community disaster response of Gampong Seulalah Langsa Lama in Langsa City in the event of the flood disaster. The type of this research is experimental research with phenomenology method. Data processing is done by performing data organizing, reading, and coding. The researchers also made an edge note of the data obtained. Furthermore, researchers condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
1
1
0
1
Order By: Relevance
“…A study in Langsa city in Indonesia, showed low level of community flood disaster preparedness (Afrian et al, 2018), similar to our study; and some of the reasons included poor public awareness, poor disaster risk reduction such as building in flood prone areas, blockage of drainage, poor disaster warning system, poverty and level of education (Afrian et al, 2018).…”
Section: Discussionsupporting
confidence: 85%
“…A study in Langsa city in Indonesia, showed low level of community flood disaster preparedness (Afrian et al, 2018), similar to our study; and some of the reasons included poor public awareness, poor disaster risk reduction such as building in flood prone areas, blockage of drainage, poor disaster warning system, poverty and level of education (Afrian et al, 2018).…”
Section: Discussionsupporting
confidence: 85%
“…Informasi yang mereka miliki masih tahap mengetahui bahwa banjir akan terjadi apabila hujan deras. Hal tersebut senada dengan hasil dari penelitian serupa pada Gampong Seulalah Kota Langsa yang menyatakan bahwa "Most of the gampong resident know that flood disaster is a threat in their environment, but their Jurnal Pendidikan Geografi: Kajian, Teori, dan Praktik dalam Bidang Pendidikan dan Ilmu Geografi Tahun 24, Nomor 2, Jun 2019, Hal 132-144 knowledge is only limited to rain as the main cause of this problem" (Afrian, Islami, Akob, Hamdani, & Sofyan, 2018).…”
Section: Identifikasi Dan Penempatan Informasiunclassified
“…The main cause of flooding in Langsa City comes from high rainfall. If heavy rain falls continuously, 2 the water will not go directly into the drainage system, but the falling water will become a pool [6].…”
Section: Introductionmentioning
confidence: 99%